PAW34 Mutations in OPA1 expand the clinical phenotype of mitochondrial disease. Issue 11 (22nd October 2010) - Chinnery, P; Jackson, M; Amati-Bonneau, P; Yu-Wai-Man, P; Gorman, G; Duffey, P; Baker, M; Zeviani, M; Horvath, R; Miller, J
Abstract : OPA1 codes for a mitochondrial fusion protein found on the inner mitochondrial membrane. Mutations in OPA1 are the most common cause of autosomal dominant optic atrophy (DOA), and until recently, this was thought to be a pure ocular disorder. By studying 104 patients from 45 independent families we have defined the clinical spectrum of this new multisystem mitochondrial disease, which we have called DOA+. We show that extra-ocular neurological complications affect ∼20%, and include sensorineural deafness in childhood, followed by ataxia, myopathy, peripheral neuropathy and progressive external ophthalmoplegia in the very late stages. We have also identified novel clinical presentations mimicking hereditary spastic paraplegia, and a multiple sclerosis-like illness resembling "Harding's disease", first described in patients with Leber hereditary optic neuropathy. We show that the risk of DOA+ is greatest in patients with mis-sense mutations, particularly those affecting the GTPase region of the protein, and that secondary mitochondrial DNA defects are likely to be responsible for the extra-ocular features. Individuals with DOA+ phenotypes also had significantly worse visual outcomes, and careful surveillance is therefore mandatory to optimise the detection and management of neurological disability in a group of patients with already significant visual impairment.